Analisis Resepsi Khalayak mengenai Hipnotis dalam Program â€œGaris Tangan (Episode 195)â€ ANTV - Santi Delliana; Ayu Wiranti (Research and Community Service INSTITUT TEKNOLOGI DAN BISNIS KALBIS, 2023)
People see in reporting that hypnotic is usually used as a fraud mode, increasing people's concerns about hypnotics. Various impressions in the media also show that hypnotics are now used as a hypnotherapy method, but hypnotics are used in the media as an entertainment concept. The Garis Tangan program is an entertainment program that brings the theme of a new concept about hypnosis. From the program, the purpose of this research is to find out how the Bandung Hypnotic Community interprets hypnotics in a reality show program,